Effect of six-week traditional resistance and functional training on functional performance in female netball players - Dimitrije Kovac; Zarko Krkeljas; Ranel Venter (BMC, 2022)
Abstract Background Improving the quality of functional movements in athletes generally requires additional training targeting specific functional deficiencies. However, well-rounded, traditional strength and conditioning program should also improve player's movement quality. Therefore, the primary aim of this study was to compare the effect of two different six-week interventions on the functional score of female netball players. Methods In a randomized controlled study, players were divided into control and intervention group. Both groups completed identical six-week strength and conditioning program, with the intervention group also completing additional corrective exercises three sessions per week during the same period. Results The FMS® score was significantly higher in the intervention group after 6-week program (f = 9.85, p = 0.004). However, the differences in total score may be attributed mainly to differences between groups in active straight leg raise (p = 0.004) and trunk stability push-up test (p = 0.02), as other individual tests demonstrated similar time and group effect. Conclusion These results indicate that although FMS® based intervention may improve overall functional movement score, the athletes in both groups have demonstrated similar improvements in most of the individual tests. Hence, a well-rounded strength and conditioning program incorporating athlete-specific exercises based on limitations identified in the functional movement screen, may result in a balanced training strategy and reduce the need for supplementary functional training sessions.